On Hermite-Hadamard Type Inequalities for Coordinated Convex Functions via (p,q)-Calculus - Fongchan Wannalookkhee; Kamsing Nonlaopon; Jessada Tariboon; Sotiris K. Ntouyas (Mathematics, 2021)
In this paper, we define <semantics>(p,q)</semantics>-integrals for continuous functions of two variables. Then, we prove the Hermite-Hadamard type inequalities for coordinated convex functions by using <semantics>(p,q)</semantics>-integrals. Many results obtained in this paper provide significant extensions of other related results given in the literature. Finally, we give some examples of our results.